#TITLE_ALTERNATIVE# - AISYAH MUKARROMAH (11613026), RATU
Hypercholesterolemia is a condition when the cholesterol levels in the blood exceeds normal limits. Increased levels of cholesterol in the blood may become a risk factor for some diseases such as atherosclerosis, coronary heart disease, stroke, and metabolic syndrome. The causes of hypercholesterolemia include heredity, high-fat diet, lack of exercise, and smoking. Lifestyle changes are an effective therapy for lowering cholesterol levels and as an initial therapy recommended by Adult Treatment Panel III (ATP III). The study aims to examine the effect of education to lifestyle and decreased total cholesterol levels. The study uses prospective design through interviews with 32 subjects that are grouped into 2 groups; education and non-education groups that consist 16 people in the each group. The results show that the lifestyle quality of education groups was better than the non-education groups. Based on sports habits and fiber consumption, both fruits and vegetables, education groups have higher habits than non-education groups. Based on the consumption habits of high cholesterol foods, the education group more high aware to cholesterol intake than non-education groups. For the last result, comparative value of the first and the last total cholesterol levels showed that education had an effect on decreasing total cholesterol levels (p<0,05).